Resonant vibrational-electronic coupling between photosynthetic excitons is inadequately described by reduced basis sets - Sahu, Amitav (2020)
Ultrafast internal conversion between excited states of photosynthetic pigments has been a subject of intense spectroscopic interest owing to its near unity quantum yield. Of particular interest is the possibility of strong non-adiabatic mixing between vibrational and electronic degrees of freedom, termed as vibronic mixing, caused by resonances between exciton energy gaps and dense low-frequency vibrational spectrum of photosynthetic pigments. Several reports have implicated coherent superpositions of vibronically mixed excitons to explain experimental signatures, and vibronic exciton quantum dynamical simulations have further suggested a possible functional role for quantum superpositions in enhancing the rates of energy and charge delocalization. A key question which arises in this context is -- what are the unique properties of excitons coupled through resonant vibronic coupling, and whether these properties could be well approximated in basis sets with reduced vibrational dimensionality without over-simplifying the expected excited state dynamics? The above question will be the main theme of this presentation.